Hermeneutika Hadis Muhammad Syahrur dan Kedudukan Nabi dalam Hukum Islam - Sa'adah, Hitna Bis; Masruhan, Masruhan (el Buhuth: Borneo Journal of Islamic Studies, 2025)
This article discusses Muhammad Syahrur's hermeneutical approach in understanding hadith and its implications for the position of the Prophet Muhammad in the Islamic legal system. Syahrur, as a contemporary Syrian thinker, offers a rational and contextual approach to religious texts, including hadith, which have been positioned as the main source of law after the Qur'an. In his hermeneutical framework, Syahrur distinguishes between “nusus” (text) and “fahm” (understanding), and emphasizes the importance of contextual reading of hadith by considering the times and social realities. He views that the authority of the Prophet as the bearer of revelation is limited in a particular historical context, so that not all actions of the Prophet are automatically binding as the basis of universal law. This view raises a critical discourse on the authority of hadith in the construction of Islamic law and opens a wider space for ijtihad for Muslims today. The article also examines the responses to Shahrur's ideas, both from supporters of Islamic thought reform and from those who maintain the traditional approach. In doing so, it seeks to contribute to the contemporary discourse on the methodology of understanding hadith and the role of the Prophet in the modern Islamic legal system.